Phraselogical Images of the World as Linguistic Study Objects - O’rinbekovna , Ubaydullayeva Muattar (Miasto Przyszłości, 2023)
The linguistic environment and phraseological representation of the universe are discussed in this article. We analyze the function and significance of phraseological units in the language universe.